The inevitable gateway from prostitution: a post-colonial study on Eka Kurniawan’s Beauty is a wound - Risalat, Iqra (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2021.